Special Education in rural schools: a clipping about the educational inclusion in the interior of the state of Espírito Santo - Andressa Dias Koehler; Taiane Christo Chaga; Lucimar Aparecida Stein Kuster (Universidade Federal do Norte do Tocantins, 2020)
This study discusses the special education developed in rural schools from exploratory research made by means of a semi-structured questionnaire applied to teachers of two rural schools, located in the interior of the State of Espirito Santo. The study aims to analyse how has occurred the inclusion of the target students of the special education in these institutions based on testimony of the teachers. The research reveals that some impasses of these schools in relation to inclusion this target group are similar to urban contexto, for example, in the formation of tearchers and need of public investment. However, when are added the geographical, social and cultural realities in the campesino contexto, there is a need of a look more applied to special education in rural schools, thinking about a specialized educational attendance and formation of articulated teachers to local realities of small farmers, quilombolas, indian communities, fishemen, squatters, riverside communities, farm workers, landless workers and everyone else who lives in the countryside.